Criminalization of HIV transmission and exposure: in search of rights-based public health alternatives to criminal law. (August 2011) - Csete, Joanne; Elliott, Richard
The use of criminal law to address HIV transmission and exposure has been misguided and ineffective. Criminalization of HIV transmission and exposure raises difficult legal questions: what is the appropriate degree of mental culpability to trigger criminal prosecution? Is it appropriate for the law to equate nondisclosure of (known) HIV-positive status to a sexual partner with rape (as the law does in some jurisdictions)? Can it be justified to treat mere nondisclosure of HIV status as equivalent to the intent to cause harm? To what extent will the law recognize circumstances that mitigate harm, risk of harm and mental culpability, such as safer sex practices and low viral load, in mitigating the application of criminal sanctions? Sound guidance on avoiding the misuse of the criminal law in this area has been developed, but unfortunately many criminal laws in this area allow for prosecution even in cases where there is little justification. It is reasonable to expect that the use of these laws contributes to HIV-related stigma and discrimination, particularly when cases are portrayed sensationally in mass media. The harm caused by unjustified prosecutions and convictions and stigma is not counterbalanced by any evidence of public health benefits of this use of criminal law. These laws should urgently be repealed or reformed as part of a shift to strategies centered on human rights.